(untitled) (Dhaka University Journal of Science, 2013)
Chitin was extracted from the fish scales of Labeo rohita and chitosan was successfully prepared from it by deacetylation reaction. The prepared chtiosan was characterized by FT-IR spectral analysis and degree of decetylation was determined by pH-metric titration. The molecular weight of chitosan was estimated by viscometric method. Chitosan was converted into its carboxymethyl derivative using alkali and monochloroacetic acid. The prepared carboxymethyl chitosan was characterized by FT-IR spectral analysis and degree of substitution was estimated. Dhaka Univ. J. Sci. 61(1): 145-148, 2013 (January) DOI: http://dx.doi.org/10.3329/dujs.v61i1.15116